Impact of prior bortezomib therapy on the incidence of lenalidomide-induced skin rash in multiple myeloma: a propensity score-matched multi-institutional cohort study. Issue 12 (15th October 2019) - Dote, Satoshi; Ito, Kaori; Itakura, Shoji; Yasu, Takeo; Hira, Daiki; Noda, Satoshi; Yamada, Shigeki; Kobayashi, Yuka; Terada, Tomohiro
Abstract: This retrospective cohort study was conducted to investigate the association between prior bortezomib (BOR) therapy and lenalidomide (LEN)-induced rash in multiple myeloma (MM) patients. Eligible MM patients initially treated with LEN were divided into two propensity score-matched cohorts according to the presence or absence of prior BOR therapy. The primary endpoint of the study was rash incidence. We evaluated 144 patients and each cohort contained 43 patients after matching propensity-score. Rash incidence significantly decreased in patients with prior BOR therapy than in those without (30% vs. 53%, p < .05). Moreover, patients with rash showed a significantly higher incidence of eosinophilia within 1 month after LEN initiation than those without rash. Our findings indicate that prior BOR therapy may reduce the incidence of LEN-induced rash, which may be characterized by eosinophilia. Accordingly, in patients who discontinued LEN therapy due to rash, LEN re-treatment may be successful after BOR therapy.